Dynamic Grafting of Carboxylates onto Poly(Vinyl Alcohol) Polymers for Supramolecularly‐Crosslinked Hydrogel Formation. Issue 20 (22nd September 2022) - Wong, Joey Hui Min; Ting Tan, Rebekah Pei; Chang, Jun Jie; Ow, Valerie; Yew, Pek Yin Michelle; Chee, Pei Lin; Kai, Dan; Loh, Xian Jun; Xue, Kun
Abstract: Supramolecular hydrogels have attracted considerable interest due to their unique stimuli‐responsive and self‐healing properties. However, these hydrogel systems are usually achieved by covalent grafting of supramolecular units onto the polymer backbone, which in turn limits their reprocessability. Herein, we prepared a supramolecular hydrogel system by forming dynamic covalent crosslinks between 4‐carboxyphenylboronic acid (CPBA) and polyvinyl alcohol (PVA). The system was then further crosslinked with either calcium ions or branched polyethylenimine (PEI) to generate hydrogels with distinctly different properties. Incorporation of calcium ions resulted in the formation of hydrogels with higher storage modulus of 7290 Pa but without self‐healing properties. On the other hand, PEI‐crosslinked hydrogel (PVA‐CPBA‐PEI) exhibited >2000% critical strain value, demonstrated high stability over 52 days and showed sustained antibacterial effect. A combination of supramolecular interactions and dynamic covalent crosslinks can be an alternate strategy to fabricate next‐generation hydrogel materials. Abstract : Functionalization of PVA backbone with carboxyphenylboronic acid results in the formation of a suprapolymeric conjugate with dynamically attached carboxylate units, which can be subsequently crosslinked to form supramolecular hydrogels through ionic and electrostatic interactions. The properties of the hydrogels can be tuned effectively by varying the supramolecular interactions.